INFLATION PRESSURE AND INTEREST RATE RESILIENCE IN INDONESIAN MINING STOCK PRICES - Nove Anggrayini (UIN Sunan Gunung Djati Bandung, 2026)
This study uses a quantitative design with secondary data from Statistics Indonesia, Bank Indonesia, and the Indonesia Stock Exchange to examine how inflation and interest rates affect the stock prices of mining companies listed on the IDX during 2020–2022. The three-year time window encompasses the pandemic shock, stalled recovery, spikes in inflation, and tighter monetary policy an ideal macro-financial laboratory. Purposeful sampling selected 60 of the 67 mining companies in the energy sector, resulting in 180 company-year observations. All classical assumptions were met, allowing for estimation through multiple linear regression. The results are clear. Inflation has a negative and significant impact on mining stock prices. However, interest rates exhibit a positive and significant effect contrary to conventional predictions. Together, the two variables explain 98.7% of the variation in stock prices. This high explanatory power suggests that fluctuations in this sector are almost entirely driven by these two macro factors. The direction of the interest rate effect requires special attention. Standard theory holds that rising interest rates raise the cost of capital, attracting investors to fixed-income assets, and depressing equity valuations. However, in commodity-based sectors, tightening is often accompanied by rising global commodity prices driven by strong demand or supply disruptions, which improves mining companies' earnings prospects. Consequently, mining stocks can rise precisely when monetary authorities tighten policy. This finding not only reinforces the centrality of macroeconomic variables in mining stock fluctuations but also challenges conventional transmission channels: in resource industries, the interest rate-stock price relationship can operate inversely. Indeed, this counterintuitive pattern warrants further examination.